Impact of advertising on consumer's buying behavior among undergraduate students in Universiti Utara Malaysia - Yuhalis, Abdul Hadi (2016)
In the new era and the modern world advertising industry is experiencing fast extraordinary changes. Commonly, advertising is one of platform for communication that used to inform, persuade and remind consumers about the existence of certain products or services in the certain market. Advertising, shows as a favorite type to students in influencing their buying behavior, however, students tend to follow the perception and the buying pattern of the family. Moreover, student buying behavior affected by the family when they take control of the student’s economic situation by manipulating the amount of allowance and controlling the spending power. Thus, the main of the study to examine the factors that influence students buying behavior, according to consumer opinion, such as qualities of product advertise, price of product advertises, the brand image of product advertises and celebrity endorsement. This study was conducted towards the opinion of undergraduate full time students in Universiti Utara Malaysia. The total of 400 questionnaires was distributed, however, only 392 can be analyzed. The outcomes showed after analysis by using the Statistical Package for Social Science Program (SPSS) software version 22.0, that the qualities of product advertises, price of product advertises, the brand image of product advertises has a positive influence on consumer’s buying behavior. Besides that, the implication of the theory and practice as well as suggestions for future research are also discussed in this study.